Improving Activity and Mathematic Learning Outcomes of Students by Using Inquiry Learning Method - Ika Febrianti (Universitas Islam Jember, 2016)
The purpose of the research to describe the activities and student learning outcomes during the application of mathematics learning using inquiry method. To find out whether or not the increase in student activity during mathematics learning by using inquiry learning method. Toknow whether or not the increase in student learning outcomes after following the learning of mathematics by using inquiry method. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIB at MTs Negeri Bodowoso 1. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used are qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: inquiry, students activity, and mathematical learning outcomes